Type III receptor serine/threonine kinases in GtoPdb v.2025.3 (IUPHAR/BPS Guide to Pharmacology CITE, 2025)
Type III serine/threonine kinase is often referred to as an accessory protein. While it has no known enzymatic activity, it can regulate the signalling of RSTKs [3, 2].